2015
DOI: 10.3109/00365521.2015.1095350
|View full text |Cite
|
Sign up to set email alerts
|

Association of endoscopic ultrasonographic parameters and gastrointestinal stromal tumors (GISTs): can endoscopic ultrasonography be used to screen gastric GISTs for potential malignancy?

Abstract: The preliminary results show that large gastric GISTs with cystic change and surface ulceration may associate with a risk of malignancy, warranting more aggressive management. Nevertheless, the tumor size is more important than other factors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
18
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(22 citation statements)
references
References 7 publications
3
18
0
1
Order By: Relevance
“…However, a study by Kim et al[33] found no CT features, other than size, to be correlated with biological behavior and prognosis of GIST. This finding was confirmed very recently by Chen et al[34]; specifically, that retrospective analysis of 110 patients who underwent endoscopic ultrasonography identified tumor size as an independent risk factor for malignancy ( P ≤ 0.0001) but not for calcification ( P = 0.667).…”
Section: Discussionsupporting
confidence: 72%
“…However, a study by Kim et al[33] found no CT features, other than size, to be correlated with biological behavior and prognosis of GIST. This finding was confirmed very recently by Chen et al[34]; specifically, that retrospective analysis of 110 patients who underwent endoscopic ultrasonography identified tumor size as an independent risk factor for malignancy ( P ≤ 0.0001) but not for calcification ( P = 0.667).…”
Section: Discussionsupporting
confidence: 72%
“…Endoscopic ultrasonography (EUS) is recommended to narrow the differential diagnosis of SETs as it can help ascertain key pathologic characteristics such as depth, size, and the layer of origin within the gastrointestinal wall. Tumor size, echo patterns, extraluminal margins, and cystic spaces on EUS have been suggested to aid in distinguishing between benign and malignant lesions [5,6]. However, the diagnostic efficacy of EUS is limited, as it does not provide histopathologic diagnosis.…”
mentioning
confidence: 99%
“…Size larger than 20 mm, presence of cystic spaces, surface ulceration, irregular borders, and echogenic foci are unique features predictive of the malignant potential of GISTs and, therefore, worse outcomes [6, 38]. Among them, tumor size is the most important factor.…”
Section: Discussionmentioning
confidence: 99%